2008
DOI: 10.1002/bjs.6057
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G4-related sclerosing cholangitis in patients resected for presumed malignant bile duct strictures

Abstract: Features of autoimmune-like bile duct disease were seen in almost half (15 of 32) of patients with benign hilar strictures resected for presumed hilar cholangiocarcinoma. Frank IgG(4)-related sclerosing disease was found in only two of the 15 patients with autoimmune-like bile duct disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 35 publications
2
82
0
1
Order By: Relevance
“…Recently, IgG4-related lymphoplasmacytic sclerosing disease was observed in patients with strictures of the pancreatic duct mimicking carcinoma [20] . In a study from our center, it was shown that IgG4-related sclerosing disease also occurs in patients with benign proximal bile duct strictures [21] . In the present series, two of the ten patients with benign proximal bile duct strictures showed infiltration by IgG4-plasma cells with histological features suggestive of an autoimmune disorder.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, IgG4-related lymphoplasmacytic sclerosing disease was observed in patients with strictures of the pancreatic duct mimicking carcinoma [20] . In a study from our center, it was shown that IgG4-related sclerosing disease also occurs in patients with benign proximal bile duct strictures [21] . In the present series, two of the ten patients with benign proximal bile duct strictures showed infiltration by IgG4-plasma cells with histological features suggestive of an autoimmune disorder.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, establishing a definitive diagnosis was challenging in this case. In IgG4-RD patients, malignant tumors are often suspected, and obtaining the differential diagnosis is often very difficult (9). Most patients with IgG4-related cholecystitis exhibit diffuse, circumferential thickening of the gallbladder wall associated with IgG4-SC or AIP.…”
Section: Discussionmentioning
confidence: 99%
“…4 Before surgery, it was difficult to deny the possibility of cancer because the imaging of IgG4-SC was similar to cancer. PSC was suspected in cases in which bile duct stenosis occurred.…”
Section: Discussionmentioning
confidence: 99%